Quality of Life of Pharmacy Students with Polycystic Ovarian Syndrome in South India: A Cross-Sectional Study - Mugada, Vinodkumar; Mandarapu, Krishna Priya (Makara Journal of Health Research, 2021)
Background: One in five women in India suffers from polycystic ovarian syndrome (PCOS). In this study, we aimed to evaluate the quality of life of pharmacy students suffering from PCOS and provide awareness through counseling. Methods: A cross-sectional study was conducted on 103 students with PCOS for 6 months. The Polycystic Ovarian Syndrome Quality of Life (PCOSQ) questionnaire was used to determine the quality of life. Results: The prevalence of PCOS in our study was 39.5%. The mean age of the students was 21.1 (±1.8) years. The mean duration of the disorder was 17.8 (±13.0) months. More than three-quarters (77.6%) of them were under medications. Menstrual problems had a severe negative impact on the quality of life. In addition, emotion, body hair, weight gain, and infertility had a moderate impact on the quality of life. A significant association was observed among sleeping habits and infertility problems (p = 0.014), physical activity, weight (p = 0.032), and menstrual problems (p = 0.042). Conclusions: Menstrual problems have a significant impact on the quality of life of students with PCOS. Moreover, health science students must develop an awareness of prevalent noncommunicable diseases to help themselves and the society.